(untitled) (Journal of Atomic and Molecular Sciences, 2013)
The p53-MDM2 interaction has been an important target of drug design curing cancers. In this work, Molecular dynamics (MD) simulation coupled with molecular mechanics/Poisson Boltzmann surface area method (MM-PBSA) is performed to calculate binding free energy of peptide inhibitor pDI6W to MDM2. The results show that van der Waals energy is the dominant factor of the pDI6W-MDM2 interaction. Cross-correlation matrix calculated suggests that the main motion of the residues in MMDM2 induced by the inhibitor binding is anti-correlation motion. The calculations of residue-residue interactions between pDI6W and MDM2 not only prove that five residues Phe19’, Trp22’, Trp23’, Leu26’ and Thr27’ from pDI6W can produce strong interactions with MDM2, but also show that CH-π, CH-CH and π−π interactions drive the binding of pDI6W in the hydrophobic cleft of MDM2. This study can provide theoretical helps for anti-cancer drug designs.